Chondrocyte expansion is associated with loss of primary cilia and disrupted hedgehog signalling - Thompson, C; Plant, J; Wann, A; Bishop, C; Novak, P; Mitchison, H; Beales, P; Chapple, J; Knight, M (AO Research Institute Davos, 2017)
Tissue engineering-based therapies targeting cartilage diseases, such as osteoarthritis, require in vitro expansion of articular chondrocytes. A major obstacle for these therapies is the dedifferentiation and loss of phenotype accompanying chondrocyte expansion. Recent studies suggest that manipulation of hedgehog signalling may be used to promote chondrocyte re-differentiation. Hedgehog signalling requires the primary cilium, a microtubule-based signalling compartment, the integrity of which is linked to the cytoskeleton. We tested the hypothesis that alterations in cilia expression occurred as consequence of chondrocyte dedifferentiation and influenced hedgehog responsiveness. In vitro chondrocyte expansion to passage 5 (P5) was associated with increased actin stress fibre formation, dedifferentiation and progressive loss of primary cilia, compared to primary (P0) cells. P5 chondrocytes exhibited ~50 % fewer cilia with a reduced mean length. Cilia loss was associated with disruption of ligand-induced hedgehog signalling, such that P5 chondrocytes did not significantly regulate the expression of hedgehog target genes (GLI1 and PTCH1). This phenomenon could be recapitulated by applying 24 h cyclic tensile strain, which reduced cilia prevalence and length in P0 cells. LiCl treatment rescued cilia loss in P5 cells, partially restoring hedgehog signalling, so that GLI1 expression was significantly increased by Indian hedgehog. This study demonstrated that monolayer expansion disrupted primary cilia structure and hedgehog signalling associated with chondrocyte dedifferentiation. This excluded the possibility to use hedgehog ligands to stimulate re-differentiation without first restoring cilia expression. Furthermore, primary cilia loss during chondrocyte expansion would likely impact other cilia pathways important for cartilage health and tissue engineering, including transforming growth factor (TGF), Wnt and mechanosignalling.